2016
DOI: 10.1089/bfm.2015.0094
|View full text |Cite
|
Sign up to set email alerts
|

Breastfeeding Associated with Reduced Mortality in Women with Breast Cancer

Abstract: A total breastfeeding history >6 months and pregnancy are associated with both greater overall and breast cancer-specific survival for women diagnosed with breast cancer, having lived long enough for other causes of death to contribute substantially to mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 24 publications
(41 reference statements)
0
5
0
Order By: Relevance
“…In addition, breastfeeding has immediate and lasting benefits on maternal health, as demonstrated by several studies, which have shown a reduction in risk for some cancers, such as breast cancer, ovarian cancer, and endometrial cancer [4][5][6][7][8][9]. Benign breast disease does not usually interfere with a woman's ability to breastfeed [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, breastfeeding has immediate and lasting benefits on maternal health, as demonstrated by several studies, which have shown a reduction in risk for some cancers, such as breast cancer, ovarian cancer, and endometrial cancer [4][5][6][7][8][9]. Benign breast disease does not usually interfere with a woman's ability to breastfeed [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…The reproductive history of a woman is closely linked to breast cancer risk [810]. The first full-term pregnancy (FTP) is a key event in the determination of the fate of the mammary gland in a woman.…”
Section: Introductionmentioning
confidence: 99%
“…The study also found no association between histological type and survival in common with other works. 49,50 Lööf-Johanson et al 51 reported that there was a higher survival rate for women with primary BC if overall breastfeeding was longer than 6 months and/or if they had at least one pregnancy. The results of our study were in line with other studies that reported different results.…”
Section: Resultsmentioning
confidence: 99%